Genetically Modified Organisms: Adapting Regulatory Frameworks for Evolving Genome Editing Technologies - Martinez-Fernandez, C; Kessi-Perez, E (BioMed Central Ltd, 2022)
Genetic modification of living organisms has been a prosperous activity for research and development of agricultural, industrial and biomedical applications. Three decades have passed since the first genetically modified products, obtained by transgenesis, become available to the market. The regulatory frameworks across the world have not been able to keep up to date with new technologies, monitoring and safety concerns. New genome editing techniques are opening new avenues to genetic modification development and uses, putting pressure on these frameworks. Here we discuss the implications of definitions of living/genetically modified organisms, the evolving genome editing tools to obtain them and how the regulatory frameworks around the world have taken these technologies into account, with a focus on agricultural crops. Finally, we expand this review beyond commercial crops to address living modified organism uses in food industry, biomedical applications and climate change-oriented solutions. © 2022, The Author(s).